2018
DOI: 10.1186/s12886-018-0788-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between glaucoma severity and driving cessation in subjects with primary open-angle glaucoma

Abstract: BackgroundThe aim of this study, which included a baseline cross-sectional study and a 3-year follow-up prospective study, was to investigate the association between glaucomatous visual field damage and driving cessation in subjects with primary open-angle glaucoma (POAG).MethodsA total of 211 POAG subjects divided into 3 groups according to POAG severity (mild, moderate, or severe) in the better eye were enrolled along with 148 control subjects; subjects were asked about changes in their driving status. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Raw data on studies reporting on MVCs15–81 and driving cessation70–73 82–115 can be found in online supplemental appendix 4A,B, respectively, with additional narrative summaries. Meta-analyses on associations are presented in online supplemental appendix 5A,B; only 25 studies could be meta-analysed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raw data on studies reporting on MVCs15–81 and driving cessation70–73 82–115 can be found in online supplemental appendix 4A,B, respectively, with additional narrative summaries. Meta-analyses on associations are presented in online supplemental appendix 5A,B; only 25 studies could be meta-analysed.…”
Section: Resultsmentioning
confidence: 99%
“…There were 13 studies (n=21 939) investigating associations between glaucoma and the likelihood of driving cessation with estimates ranging from an increased risk of 1.3 to increased odds of 4 70–72 87 91 92 99 100 103 109–111 113. The meta-analysis in online supplemental appendix 5B suggests a diagnosis of glaucoma to increase the risk of driving cessation by 63% (95% CI 1.20% to 2.19%; p<0.01)87 91; however, this analysis only contained two studies.…”
Section: Resultsmentioning
confidence: 99%
“…A sample size of 94 was calculated by Rao soft calculator keeping confidence level 95 percent. POAG was diagnosed with at least two readings of IOP above 21 mm Hg by Goldmann tonometry, an open angle on gonioscopy or Visual field defects on Humphrey perimetry (14). Exclusion criteria included Patients presenting with secondary causes of glaucoma, normal tension glaucoma and acute angle closure glaucoma.…”
Section: Methodsmentioning
confidence: 99%
“…A thorough ophthalmic examination of POAG patients and controls was carried out by an experienced eye specialist. Glaucoma cases were graded as mild, moderate and severe based on visual field defects on Humphrey perimetry (14). A 7 ml venous blood sample was taken from POAG patients for pathology lab tests.…”
Section: Methodsmentioning
confidence: 99%
“…Diante desse contexto, uma espiral de sentimentos e comportamentos, como parar de conduzir, pode levar ao isolamento social e, em última análise, à depressão e à diminuição da mobilidade e QV (46,65,(80)(81)(82) .…”
Section: O Processamento Visual E O Risco Na Condução De Veículos No Glaucomaunclassified